Educação do campo e educação matemática crítica: processo formativo dos professores que ensinam matemática nas escolas do campo do município de Feira de Santana – Bahia - Souza, Piterson Ferreira de (2023)
The present dissertation had as its general objective to understand, from the perspective of Critical Mathematics Education, the formative process of teachers who teach mathematics in rural schools located in the districts of the municipality of Feira de Santana - Bahia. This is a qualitative, descriptive and exploratory research. The search achieved 48% of the teachers who work in rural schools (municipal and state network) in the districts of the municipality of Feira de Santana (all of them licensed), and through the analysis of official documents and application of interaction, we found that the network public school is responsible for the greater employability of education professionals, with 90% of the teachers who teach mathematics in rural schools located in the districts of Feira de Santana obtaining a degree from the State University of Feira de Santana. In addition, we noticed an absence of the debate on Rural Education and Critical Mathematics Education in initial training and it shows the existence of a flaw in this training, and how much this impacts the perception of teachers from rural schools about this teaching modality, once we found professors who will not realize any difference between the rural school and the urban school, those who seek to adapt to the rural schools, those who tend to contextualize the mathematical contents to the rural context, and finally those who will look for mechanisms to be inserted in the mathematics teaching process in view of the possibility of guaranteeing a citizenship formation in the critical perspective in the promotion of autonomous and emancipated subjects. Therefore, we conclude the need for the presence of the debate of Critical Mathematics Education and Rural Education in initial training, whatever the Higher Education Institution, and we present the Critical Mathematics Education as a theoretical possibility and an alternative for the initial training of the teacher of Mathematics, which enables a critical perception that guarantees his performance in schools, taking into account the specificities of Rural Education.